Decorating bacteria with self-assembled synthetic receptors - Lahav-Mankovski, Naama (Nat Commun, 2020)
The responses of cells to their surroundings are mediated by the binding of cell surface proteins (CSPs) to extracellular signals. Such processes are regulated via dynamic changes in the structure, composition, and expression levels of CSPs. In this study, we demonstrate the possibility of decorating bacteria with artificial, self-assembled receptors that imitate the dynamic features of CSPs. We show that the local concentration of these receptors on the bacterial membrane and their structure can be reversibly controlled using suitable chemical signals, in a way that resembles changes that occur with CSP expression levels or posttranslational modifications (PTMs), respectively. We also show that these modifications can endow the bacteria with programmable properties, akin to the way CSP responses can induce cellular functions. By programming the bacteria to glow, adhere to surfaces, or interact with proteins or mammalian cells, we demonstrate the potential to tailor such biomimetic systems for specific applications.